Endocannabinoids inhibit contextual fear memory generalization via hippocampal GABAergic synaptic transmission - Qian Ge; Jinming Zhang; Qing Huo; Jing Yu; Qiaohua Zheng; Zhaoqiang Qian; Chunling Wei; Tongtong Jiang; Yihui Liu; Zhiqiang Liu; Wei Ren; Zongpeng Sun; et al. (Proceedings of the National Academy of Sciences, 2025)
Memory generalization allows an organism to adapt to new conditions, but overgeneralization of fear or traumatic experiences can be detrimental to survival and contributes to the development of various mental disorders. However, the cellular and molecular mechanisms underlying fear memory generalization, especially in the hippocampus, remain largely unknown. In this study, utilizing a well-established mouse model of fear memory generalization, we investigated the role of endocannabinoids (eCBs)-mediated GABAergic synaptic inputs to hippocampal pyramidal neurons in regulating contextual fear memory generalization. Our results revealed that pharmacological or genetic blockade of CB1R in hippocampal CA1 resulted in overgeneralization of contextual fear memory but not fear memory expression. Subsequent investigations in conditional knockout mice revealed the involvement of CB1R in GABAergic neurons, but not those in glutamatergic neurons or astrocytes, in this overgeneralization. In addition, activation of GABA A receptors on pyramidal neurons was required for inducing overgeneralization via AM281, a CB1R antagonist. Neural mechanistic studies showed that eCBs/CB1R signaling regulates both the activity and plasticity of inhibitory synapses during generalization, highlighting the prominence of the disinhibition of CB1R in interneurons during this process. Subsequently, we delved into the downstream effects and found that eCB-dependent long-term potentiation (LTP) in CA1 pyramidal neurons was regulated by the aforementioned mechanisms. Our findings illustrate that the eCBs/CB1R signaling pathway modulates the balance between fear memory discrimination and generalization by controlling inhibitory inputs to hippocampal pyramidal neurons, accompanied by alterations in excitatory plasticity within this region.